Predicting difficulty in laparoscopic cholecystectomy preoperatively using modified Randhawa scoring system - Philip, Abhay M.; Anjarbeedu , Rakesh R. (International Surgery Journal, 2023)
Background: Laparoscopic cholecystectomy is a low-risk, minimally invasive operation and currently the standard for treatment of gallstone and gallbladder disease. Preoperative assessment of difficulty is required to prevent problems, ensure readiness, and ensure an effective course of surgery. Methods: In our work, we attempted to use a modified grading system developed by Randhawa et al. to preoperatively predict a difficult laparoscopic cholecystectomy. Age, gender, illness duration, history of prior GB disease, BMI, abdominal scar location (infra or supraumbilical), palpable gallbladder, and sonographic findings (gall bladder wall thickness, pericholecystic collection, and impacted stone) were assessed in patients who had been diagnosed with GB stones and required LC. Depending on the individual surgeon's assessment, a procedure is rated as easy, difficult, or very difficult. Results: On comparison of the test group difficulty level predicted with the gold standard of difficulty level intra op the test group has a sensitivity of 51.9 % and specificity of 100%. The test has a positive predictive value of 100% and Negative predictive value of 91.5%. The test and the gold standard agree on 154 out of 167 having a diagnostic accuracy of 92.21%. The Kappa value of 0.644 indicates very good agreement with a p value of <0.001. Area under the curve indicates 96.1% of the difficulty is predicted by the Total score and significant with p value of <0.001 Conclusions: The current modified Randhawa and Pujahari scoring method is useful and appropriate for forecasting operative outcome in laparoscopic cholecystectomy.